COVID-19-Related FAQs as a Form of Online Institutional Communication: An Exploratory Study - Katia Peruzzo (Lingue Culture Mediazioni, 2023)
The COVID-19 pandemic has affected everyone’s life, and COVID-19 prevention and control measures have altered everyone’s daily routine. Such measures have been put in place through legislative and regulatory acts, whose typical linguistic features make them not always accessible to the population they apply to. Therefore, other forms of communication have been used as a form of mediation, for instance by institutions and news media outlets, to share information on and thus facilitate the implementation of such measures among the population. This paper presents an exploratory micro-analysis of an English and an Italian webpage containing frequently asked questions (FAQs), a web genre often used for knowledge dissemination but still scarcely investigated from a linguistic perspective. The aim of the FAQs examined is to explain the provisions adopted to tackle the second wave of the pandemic (the two webpages were available online in September 2020) to a non-specialised and non-better specified audience. After briefly discussing the content distribution, the study adopts a conversation analysis perspective to identify the type of questions used and the (lack of ) question-conditioned relevance in adjacency pairs.